The Effect of Finger-Hold Therapy to Reduce Blood Pressure in Hypertension Patients - Nurul Huda (Poltekkes Kemenkes Semarang, 2026)
Background: Hypertension is a non-communicable disease with high prevalence and may cause serious complications such as stroke and heart disease. Hypertension management can be conducted through pharmacological and non-pharmacological approaches, including complementary therapies such as finger-holding therapy. Purpose: to determine the characteristics of hypertensive patients and to examine the effect of finger-holding therapy on blood pressure reduction among patients with hypertension in the working area of Puskesmas Piyungan. Methods: this study used Quasy Experimental with Nonequivalent Control Group Design. A total of 60 respondents participated. Finger-holding therapy was performed for 30 minutes once daily for three consecutive days. Blood pressure was measured before and after the intervention. The sampling technique used purposive sampling and the tests used Wilcoxon test for within-group comparison and the Mann–Whitney U test for between-group comparison Results: Univariate analysis showed that most respondents were aged >60 years, female, had a history of hypertension, were employed, and were non-smokers. Bivariate analysis revealed significant differences in systolic and diastolic blood pressure before and after intervention in the intervention group (p<0.01). Furthermore, significant differences in posttest systolic and diastolic blood pressure were found between the intervention and control groups, with p-values of <0.01 and 0.001, respectively. Conclusion: Finger-holding therapy is effective in reducing blood pressure among patients with hypertension. Keywords: finger-holding therapy, hypertension, complementary therapy